Empowering PKK Cadres through Digital Marketing Training for Local Product Promotion to Support Stunting Prevention in Banteran Village, Banyumas Regency - Kusuma, Inggar Ratna; Ambarwati, Dewi; Handayani, Erna; Riani, Evicenna naftuhah; Nurul, Nurul Fatmawati Fitriani; Safitri, Mutiara Dien (Edumedia Solution, 2025)
The high prevalence of stunting in Banteran Village, Banyumas Regency, is closely related to limited family income and a lack of community empowerment, especially among mothers who are members of the Family Welfare Movement (PKK). Most members have potential local products, yet their marketing skills remain low, limiting their ability to utilize digital platforms to improve household income. To address this issue, a community engagement program was conducted to strengthen the digital capacity of PKK members through digital marketing training. The activity, held on July 12, 2025, at the Embung Banteran Hall, applied a participatory empowerment approach consisting of two stages: material presentation and hands-on practice. Participants were introduced to the concept of digital marketing and guided to create Shopee Affiliate accounts. The results indicated that participants showed improved digital literacy, self-confidence, and skills in promoting local products online. Moreover, the activity contributed to enhancing family economic independence and demonstrated the potential of digital empowerment as an indirect approach to stunting prevention. This program emphasizes that digital skills development among women’s community groups can be an effective strategy for sustainable community empowerment and local economic growth.